Emotion and the Cardiovascular System: Postulated Role of Inputs From the Medial Prefrontal Cortex to the Dorsolateral Periaqueductal Gray - Dampney, Roger (Frontiers in Neuroscience, 2018)
The midbrain periaqueductal gray (PAG) plays a major role in generating different types of behavioral responses to emotional stressors. This review focuses on the role of the dorsolateral (dl) portion of the PAG, which on the basis of anatomical and functional studies, appears to have a unique and distinctive role in generating behavioral, cardiovascular and respiratory responses to real and perceived emotional stressors. In particular, the dlPAG, but not other parts of the PAG, receives direct inputs from the primary auditory cortex and from the secondary visual cortex. In addition, there are strong direct inputs to the dlPAG, but not other parts of the PAG, from regions within the medial prefrontal cortex that in primates correspond to cortical areas 10m, 25 and 32. I first summarise the evidence that the inputs to the dlPAG arising from visual, auditory and olfactory signals trigger defensive behavioral responses supported by appropriate cardiovascular and respiratory effects, when such signals indicate the presence of a real external threat, such as the presence of a predator. I then consider the functional roles of the direct inputs from the medial prefrontal cortex, and propose the hypothesis that these inputs are activated by perceived threats, that are generated as a consequence of complex cognitive processes. I further propose that the inputs from areas 10m, 25 and 32 are activated under different circumstances. The input from cortical area 10m is of special interest, because this cortical area exists only in primates and is much larger in the brain of humans than in all other primates.